2014
DOI: 10.1021/nn506589a
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Surface-Enhanced Raman Nanopillar Arrays Fabricated by Laser-Assisted Replication for Biomolecular Detection Using Organic Semiconductor Lasers

Abstract: Organic semiconductor distributed feedback (DFB) lasers are of interest as external or chip-integrated excitation sources in the visible spectral range for miniaturized Raman-on-chip biomolecular detection systems. However, the inherently limited excitation power of such lasers as well as oftentimes low analyte concentrations requires efficient Raman detection schemes. We present an approach using surface-enhanced Raman scattering (SERS) substrates, which has the potential to significantly improve the sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…AFM measurements were also performed in tapping mode on the SERS substrates exposed to ambient conditions ( Figure 2D and Figure 2E Figure S3). The attained metallic surface topography will lead to enhanced electromagnetic fields or the so-called hot spots [38].…”
Section: Synthesis and Deposition Of Au@citrate Npsmentioning
confidence: 99%
“…AFM measurements were also performed in tapping mode on the SERS substrates exposed to ambient conditions ( Figure 2D and Figure 2E Figure S3). The attained metallic surface topography will lead to enhanced electromagnetic fields or the so-called hot spots [38].…”
Section: Synthesis and Deposition Of Au@citrate Npsmentioning
confidence: 99%
“…The substrate was composed of an array of gold coated cyclic olefin copolymer nanopillars having a variable diameter of 60 to 260 nm. Several different nanopillar arrays have been produced to study the effect of nanocolumn diameter and spacing on Raman enhancement factors [112].…”
Section: Large Area Micro/nano Structure Arraysmentioning
confidence: 99%
“…FDTD simulations have been used extensively to study the optical properties of NPs, as reported in leading scientific publications (Li et al, 2010;Klinkova et al, 2014;Liu et al, 2015). The FDTD model was set up for Ag foil according to the AFM results with a surface roughness of Ag NPs of about 5 nm (Fig.…”
Section: Sers Effect Of Ag Foil 10mentioning
confidence: 99%